2018
DOI: 10.3390/min8040173
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Surface Transformation and Electrochemical Dissolution Process of Bornite in Bioleaching

Abstract: In this work, density functional theory (DFT) calculations, X-ray photoelectron spectroscopy (XPS) and electrochemistry analysis were combined to analyze the electrochemical dissolution process of bornite during bioleaching. DFT calculations showed that bornite was a conductor with metallic conductivity. The formula of bornite may be (Cu +) 5 Fe 3+ (S 2−) 4 and the surface reconstruction of (111)-S surface was discussed. Electrochemistry and XPS analysis showed that bornite tended to be directly oxidized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The Cu LMM peak of the ore is located at 569.2 eV (Figure 9b). On the 7th and 21st day, the Cu LMM peaks of the leached residues are located at 568.9 eV and 568.5 eV, respectively, which is also consistent with the binding energy value (568.5 eV) of the previously reported CuS LMM peak [20,38,39].…”
Section: X-ray Photoelectron Spectroscopy Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…The Cu LMM peak of the ore is located at 569.2 eV (Figure 9b). On the 7th and 21st day, the Cu LMM peaks of the leached residues are located at 568.9 eV and 568.5 eV, respectively, which is also consistent with the binding energy value (568.5 eV) of the previously reported CuS LMM peak [20,38,39].…”
Section: X-ray Photoelectron Spectroscopy Analysissupporting
confidence: 89%
“…Yang et al [19] used XRD and XPS to characterize the intermediary species during bornite bioleaching by mixed moderately thermophilic culture, which suggested that bornite can be transformed into chalcocite, chalcopyrite, and covellite. Furthermore, Zhao [20] found that bornite tended to be directly oxidized to CuS, FeOOH, and S 0 on the surface in bioleaching by using moderately thermophilic culture.…”
Section: Introductionmentioning
confidence: 99%
“…the electrical properties of the a‐NC‐A and a‐NC‐F films are presented in Figure S29, Supporting Information). We note that owing to the increase in S by a slight decrease in σ, which is due to the creation of less conductive iron oxide or iron oxide hydroxide by partial oxidation of NCs after storing in ambient condition, [ 99–102 ] the maximum PF and ZT of a‐NC‐C films improved over 1.2 mW m −1 K −2 and 0.042, respectively. Subsequently, we investigated the applicability of highly conductive a‐NC‐C films to conducting films.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent article by Chinese researchers, based on the cyclic voltammetry and XPS data, it was shown that the oxidation of bornite proceeds intensively at a potential of more than 0.3 V relative to the silver-silver chloride reference electrode [50]. The main intermediate phases on the surface of bornite during oxidation are elemental sulfur, FeOOH, and CuS.…”
Section: Copper Sulfidesmentioning
confidence: 99%